Agama Dan Ekonomi Kaum Tertindas - Yunus, Muh. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
As what Weber and Mc. Lelland view, it is assumed that values in certain religion and culture are believed to be able to influence the followers' behavior which are implied on the economic growth. Although indirectly they influence the economic development. Although Islam teaches about the work culture, the reality shows that Indonesian economy has been well-develop yet. Religion (Islam) as Weber criticizes, does not result in capitalism industrialization as the motivator of economic development because the culture is in line with